Dynamics Of Cross-Sector Collaboration In The Implementation Of Food Diversification Policies In Barru Regency - M. Akbar; Alwi Alwi; A. Ariyadi (Journal of Government Science Studies, 2026)
The implementation of food diversification policies is a strategic effort to achieve sustainable food security that is not dependent on a single major food commodity. The success of this policy is largely determined by the ability of local governments to build cross-sectoral collaboration involving state and non-state actors. This study aims to analyze the dynamics of cross-sector collaboration in the implementation of food diversification policies in Barru Regency, focusing on the roles of actors, inter-actor relations, policy conflicts, community participation, and factors that influence the effectiveness of policy implementation. This study uses a qualitative approach with a descriptive-analytical design. Data collection techniques were carried out through in-depth and semi-structured interviews with key actors selected through purposive sampling, including the Head of the Barru Regency Agriculture and Food Security Office, the Chair of Commission II of the Barru Regency DPRD, the Head of the Agricultural Extension Center (BPP), the Chair of GAPOKTAN, the Chair of KWT, representatives of supporting NGOs, and academics. Data analysis was carried out through data reduction, data presentation, and thematic conclusion drawing by linking field findings to the theoretical framework of policy collaboration and social capital. The results of the study show that the implementation of food diversification policies in Barru Regency is supported by relatively structured and complementary cross-sectoral collaboration. State actors play a role in policy formulation, coordination, supervision, and program implementation, while non-state actors play a role in the internalization of policies at the community and household levels. The relationship between actors shows an adaptive coordination pattern, in which differences in views and interests are managed through communication and deliberation mechanisms. The participation of community organizations and the involvement of individual citizens are important social capital that strengthens the effectiveness and sustainability of policies. This study concludes that the success of food diversification in Barru Regency is highly dependent on synergy between actors, trust, substantive participation, and policy consistency within a collaborative governance framework.